How Fragile Is Africa's Recent Growth? - Arbache, Jorge Saba; Page, John (2012)
Has Africa finally reached the path to sustained growth? We find that much of the improvement in economic performance in Africa after 1995 is attributable to a substantial reduction in the frequency and severity of growth declines in all economies and an increase in growth accelerations in mineral-rich economies. We find, however, that growth accelerations have not been generally accompanied by improvements in variables often correlated with long run growth, such as investment. We also fail to find evidence that substantial policy and governance improvements were associated with the post-1995 accelerations. We conclude that Africa's growth recovery remains fragile.